2022
DOI: 10.1111/ijfs.15799
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of silver carp surimi gel under high temperature (≥100 °C): quality changes, water distribution and protein pattern

Abstract: The effects of high‐temperature treatments (100–125 °C) on the properties of silver carp surimi gel were studied. The results showed that the gel strength and water holding capacity (WHC) of surimi gel decreased significantly (P < 0.05), with the increase of heating temperature and the prolongation of heating time, and the higher the temperature, the greater the decrease trend. Hydrophobic interaction and disulphide bonds decreased significantly, while ionic bonds increased significantly (P < 0.05), as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In this study, a Gaussian function fitting method was used to fit the deconvoluted spectra to compare the changes in protein secondary structure during storage at 4 °C and 10 °C, respectively. The results showed that the content of α-helix and β-sheet in the protein secondary structure gradually decreased with increasing storage time, while the content of the content and β-turn gradually increased, and the findings are consistent with those of previous authors [27,28]. As a result, the molecular structure of egg proteins changes in response to storage conditions, and FTIR-based techniques can provide a clearer picture of the exact changes that occur.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, a Gaussian function fitting method was used to fit the deconvoluted spectra to compare the changes in protein secondary structure during storage at 4 °C and 10 °C, respectively. The results showed that the content of α-helix and β-sheet in the protein secondary structure gradually decreased with increasing storage time, while the content of the content and β-turn gradually increased, and the findings are consistent with those of previous authors [27,28]. As a result, the molecular structure of egg proteins changes in response to storage conditions, and FTIR-based techniques can provide a clearer picture of the exact changes that occur.…”
Section: Discussionsupporting
confidence: 89%
“…Journal of Food Processing and Preservation temperatures indicates a weakening of the hydrogen bonds and a gradual unfolding of the protein molecules. decrease in α-helix content with increasing storage temperature and time in the test is therefore due to the weakening of intermolecular hydrogen bonding in egg albumin as a result of the high temperature over time [27][28][29].…”
mentioning
confidence: 99%
“…Thiobarbituric acid reactive substances Thiobarbituric acid reactive substances analysis was according to the method of Jiang et al (2022aJiang et al ( , 2022b with slight modification. Chopped samples (5 g) were dispersed in three times the volume of 7.5% trichloroacetic acid (containing 0.1% propyl gallate and 0.1% EDTA) and then homogenised.…”
Section: Peroxide Value (Pov)mentioning
confidence: 99%
“…Jiang et al . (2022a, 2022b) studied the effects of high‐temperature treatments (100–125 °C) on the properties of silver carp surimi gel, and found that high‐temperature heating resulted in protein denaturation, aggregation, crosslinking and degradation, based on the increase in trichloroacetic acid (TCA) soluble peptides and the changes in protein secondary structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation